Revisiting a Controversial Cartoon: Aseem Trivedi’s ‘Wolf Capital’ - Lakshmi Prabha P, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2025)
This article is a close reading of a controversial political cartoon drawn by cartoonist Aseem Trivedi. It examines how the cartoon texts construct a discourse of resistance and also connect to other optical metaphors within the repertoire of Indian political and cultural sign systems. This critical reading reveals that cartoons are not only a communicative event but also a vehicle of collective memory.